Non-proportionality in ratios: an alternative approach - Trigueiros, D. (2019)
This study identifies general postulates underlying the validity of the financial ratio measurement. Then, new relationships are suggested obeying the same postulates, which may replace the ratio form in the case of non-proportionality. Where proportionality holds, these relationships revert to the traditional ratio. The paper also reviews the reasons for expecting non-proportional components in ratios and presents application examples of the new relationships.